2022
DOI: 10.1186/s12957-022-02536-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomogram to predict very early recurrence of combined hepatocellular-cholangiocarcinoma after hepatic resection: a multi-institutional study

Abstract: Background and objectives Combined hepatocellular cholangiocarcinoma (cHCC) has a high incidence of early recurrence. The objective of this study is to construct a model predicting very early recurrence (VER) (i.e., recurrence within 6 months after surgery) of cHCC. Methods One hundred thirty-one consecutive patients from Eastern Hepatobiliary Surgery Hospital served as a development cohort to construct a nomogram predicting VER by using multi-vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The presence of MVI more accurately predicted higher recurrence risk and poor clinical outcomes than factors included in the Milan criteria [ 6 ]. A nomogram containing MVI, macrovascular invasion (MaVI), and CA19-9 demonstrated favorable performance in predicting very early recurrence (recurrence within 6 months after surgery) in combined hepatocellular-cholangiocarcinoma after hepatic resection [ 10 ]. Moreover, MVI determines the risk for intrahepatic or distant dissemination of malignant cells, and MVI-positive HCCs should potentially be treated with a wider resection margin to eradicate micro-metastases compared with MVI-negative tumors [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of MVI more accurately predicted higher recurrence risk and poor clinical outcomes than factors included in the Milan criteria [ 6 ]. A nomogram containing MVI, macrovascular invasion (MaVI), and CA19-9 demonstrated favorable performance in predicting very early recurrence (recurrence within 6 months after surgery) in combined hepatocellular-cholangiocarcinoma after hepatic resection [ 10 ]. Moreover, MVI determines the risk for intrahepatic or distant dissemination of malignant cells, and MVI-positive HCCs should potentially be treated with a wider resection margin to eradicate micro-metastases compared with MVI-negative tumors [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on early recurrence of HCC also highlight the independent influence of AST [27,28] and ALP [29,30] as contributing factors. Similarly, MVI has been established as a strong and independent predictor of early postoperative recurrence of cHCC-CC [12,13,15,22], likely because it is associated with the cytokines and proteins secreted by stromal cells in the tumor microenvironment that promote angiogenesis. MVI frequently involves small branches of the portal vein or hepatic vein, which results in early blood vessel dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [22] used MiVI, MaVI, and CA19-9 > 25 u/ ml as independent risk factors for very early postoperative recurrence in cHCC-CC patients and constructed a nomogram model, with AUCs of 0.77 (95%CI 0.69-0.85) and 0.76 (95% CI 0.66-0.86) in the training set and validation set, respectively. Compared to that study, our study added CT features (included tumor size, tumor margin and arterial phase peritumoral enhancement) on the basis of clinical, pathological features, and the results improved the predictive power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with Saito et al [ 25 ], we found that the larger tumor size was associated with unfavorable outcomes. In addition, another study reported that the very early recurrence nomogram contained microvascular invasion, macrovascular invasion, and CA199 level [ 27 ]. In this study, we further stratified the AYA patients with the cutoff age of 30 years old and performed the survival analysis again.…”
Section: Discussionmentioning
confidence: 99%